Global Elevation Inversion for Multiband Spaceborne Lidar: Predevelopment of Forest Canopy Height - Haowei Zhang; Wei Gong; Hu He; Yue Ma; Weibiao Chen; Jiqiao Liu; Ge Han; Zhiyu Gao; Wanqi Zhong; Xin Ma (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Compared to single-band spaceborne lidars such as the global ecosystem dynamics investigation (GEDI) and Ice, Cloud and Land Elevation Satellite-2 (ICESat-2), multiband spaceborne lidars improve the detection of the canopy and ground. However, research on geographic elevation inversion with multi-band spaceborne lidars is limited, especially in developing algorithms that fully utilize multiple wavelengths for accurate measurements. A high-precision multiband fusion algorithm (MBFA) is proposed for global geographic elevation inversion for multiband spaceborne lidar of China's Daqi-1 satellite (DQ-1), enhancing the ranging capability of the 1572 nm channel by approximately 5 times. Compared with ICESat-2, GEDI and airborne scanning data in Finland, the geographic elevation results of MBFA showed average biases of –0.09, 0.1, and –0.95 m, with root mean square errors (RMSE) of 3.68, 4.51, and 7.70 m, respectively. Accurate forest canopy heights can be obtained using the decomposed signal approach in MBFA, which has been verified in Finland. The validation results (R2 = 0.72, RMSE = 1.38 m, BIAS = –0.75 m) demonstrate the DQ-1 satellite's effectiveness in measuring canopy height. The results indicate that the MBFA model has potential for global forest canopy height extraction and carbon sink research. The proposed MBFA can also provide guide for high-precision inversion of future multiband lidar satellites.